Razvoj kompetenc, pridobljenih s študentskim delom - Ruperčič, Marko (Teorija in praksa, 2018)
In Slovenia, student work is the most common and most important way of gaining work experience while studying. We present the important role of student work in developing graduates' competencies and its influence on employability and employment. Student work is defined and located within the Slovenian labour market while the importance of prior work experience upon entering the labour market is shown. We present data on the development of competencies via student work and make comparisons with the figures on higher education graduates' expected and actual competencies.
Keywords: Employability; Employment; ključne kompetence; kompetence; Labor market; Students; Študentje; študentsko delo; Trg dela; Zaposljivost; Zaposlovanje